Analisis Yuridis Penyelesaian Sengketa Konsumen Berdasarkan UU No 8 Tahun 1999 - Rohmannudin, Rohmannudin; Hidayatullah, Iqbal; Winario, Mohd; Putri, Ramanitya Dewi (Journal of Legal Sustainability, 2024)
This study aims to analyze the effectiveness of Law No. 8 of 1999 concerning Consumer Protection in resolving consumer disputes in Indonesia, and to identify the challenges faced in its implementation. This study uses a normative legal method with a statutory approach and case analysis. Data were obtained through a literature study covering primary, secondary, and tertiary legal materials, as well as an analysis of various consumer dispute cases that have been resolved through the Consumer Dispute Resolution Agency (BPSK) and the courts. The results of the study indicate that Law No. 8 of 1999 provides a clear legal framework for the protection of consumer rights. Dispute resolution through BPSK is more efficient than litigation, but there are still obstacles, such as low legal awareness among consumers and non-compliance of business actors with BPSK decisions. These challenges hinder the optimization of consumer protection. Although Law No. 8 of 1999 has functioned well in providing protection, corrective measures are needed, including increasing socialization, strengthening BPSK, and stricter law enforcement against violations. Thus, it is expected that consumer protection can be more effective and provide better justice.